ACCEPTANCE OF INFORMATION TECHNOLOGY IN INTERNAL AUDIT PROFESSIONALS: IMPACT OF TECHNOLOGY ON COMPANIES IN JABOTABEK - Tashia, Vicario Krismon; Widuri, Rindang (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The purpose of this research is to identify organizational factors, social factors, individual factors, perceived utility, and perceived ease of use as mediating variables that influence attitudes toward use and have an effect on system use. The sample in this study is a company in Jabotabek. Sampling using convenience sampling. Data analysis using panel data regression. The findings indicated that attitudes toward use are influenced by system use and are mediated by perceived usefulness and perceived ease of use. The perceived usefulness and reported ease of use are not significantly influenced by organizational factors, social factors, or individual characteristics.